Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The exercise stated that i have to solve the recurrence using the Recursion-Tree Method. I have already finished the base part, which is $\Theta(n^{\lg3})$

But for the recursive part I'm having troubles with this sum: $cn*\sum_{i=0}^{\lg n - 1} (3/2)^i$

After resolving, I got that $T(n)=cn*n^{\lg3} - 2cn$ but this answer doesn't match $\Theta(n^{\lg 3})$ which I got using the Master Method

share|cite|improve this question
Hint: $\sum_{i=0}^{n}r^i=\frac{r^{n+1}-1}{r-1}$. – Daryl Sep 23 '12 at 7:34
up vote 2 down vote accepted

$$\sum\limits_{i=0}^{\lg n-1}(3/2)^i=\Theta((3/2)^{\lg n})\quad\text{and}\quad (3/2)^{\lg n}=2^{\lg(3/2)\lg n}=n^{\lg(3/2)}=n^{\lg3-1} $$

share|cite|improve this answer
Thanks helped a lot – Osmond Sep 24 '12 at 1:00

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.